2010
DOI: 10.4274/jcrpe.v2i1.46
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Oedema in Newly Diagnosed Type 1 Diabetes Mellitus

Abstract: Despite the essential role of insulin in the management of patients with insulin deficiency, insulin use can lead to adverse effects such as hypoglycaemia and weight gain. Rarely, crucial fluid retention can occur with insulin therapy, resulting in an oedematous condition. Peripheral or generalised oedema is an extremely rare complication of insulin therapy in the absence of heart, liver or renal involvement. It has been reported in newly diagnosed type 1 diabetes, in poorly controlled type 2 diabetes followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 14 publications
2
26
1
Order By: Relevance
“…Insulin-containing dermal patches increased urinary Na + excretion of STZinduced diabetic rats in contrast to hyperinsulinemic edema and hypertension due to increased Na + retention associated with intensive insulin therapy. 8 Our study shows that transdermal PI matrix patches can reverse the previously reported inability of the kidney to excrete Na + in STZ-diabetes mellitus. [30][31][32] Hyperinsulinemic edema and hypertension associated with intensive insulin therapy have been attributed, at least in part, to Na + retaining action of insulin.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…Insulin-containing dermal patches increased urinary Na + excretion of STZinduced diabetic rats in contrast to hyperinsulinemic edema and hypertension due to increased Na + retention associated with intensive insulin therapy. 8 Our study shows that transdermal PI matrix patches can reverse the previously reported inability of the kidney to excrete Na + in STZ-diabetes mellitus. [30][31][32] Hyperinsulinemic edema and hypertension associated with intensive insulin therapy have been attributed, at least in part, to Na + retaining action of insulin.…”
Section: Discussionsupporting
confidence: 49%
“…[30][31][32] Hyperinsulinemic edema and hypertension associated with intensive insulin therapy have been attributed, at least in part, to Na + retaining action of insulin. 8 However, literature evidence on the effects of insulin on kidney function in diabetes is conflicting and remains unclear. It would appear that renal effects of insulin depend on endogenous levels of circulating insulin and on the availability of insulin-binding sites in the kidney.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first case of insulin oedema in a child with diabetes was described by Lawrence2 in 1979. Since then, 12 cases of insulin oedema in children have been reported 3 4…”
Section: Discussionmentioning
confidence: 99%